The stealth effect from a medicinal chemist perspective: definition and updates - Fuoco, Domenico (Frontiers in Drug Delivery, 2025)
In recent years, there has been a significant increase in literature on emerging nanotechnologies, including nanoparticles, nanorobots, and exosomes, for various therapeutic applications. Additionally, politically driven research initiatives aimed at accelerating COVID-19 vaccine development have further amplified interest in nanoparticles as drug delivery systems. This article provides a personal perspective on the scientific claims surrounding nanoparticles by: (i) analyzing the historical evolution of their terminology, (ii) reviewing the most cited publications in the field, and (iii) offering a professional assessment to guide the next-generation of medicinal chemists. A key aspect of this discussion is the stealth effect, which refers to the ability of nanoparticles to evade recognition and clearance by the immune system, thereby prolonging their circulation time in the bloodstream. This property is essential for enhancing the efficacy of nanoparticle-based therapeutics by improving bioavailability and ensuring targeted drug delivery to diseased tissues. Furthermore, the continuing improvement in ligand-molecules and other functional tools have developed novel strategies and brand-new definition of delivery systems, such as Trojan Horse and Nanorobots.